Regulation of lactose permease activity by the phosphoenolpyruvate:sugar phosphotransferase system: evidence for direct binding of the glucose-specific enzyme III to the lactose permease. - Osumi, T (1982)
Interaction between the glucose-specific enzyme III (enzyme IIIglc) of the phosphoenolpyruvate:sugar phosphotransferase system and the lactose permease was studied with membrane fragments from an Escherichia coli strain that overproduces the lactose permease. Substrates of the permease markedly and specifically stimulated binding of enzyme IIIglc to the membranes. The sugar-stimulated binding of enzyme IIIglc was concluded to the specific to the lactose permease because it (i) was dependent on the amount of the permease, (ii) was promoted only by sugar substrates of the permease, and (iii) was completely eliminated by treatment of the membranes with N-ethylmaleimide in the absence (but not the presence) of thio-beta-D-digalactoside. The pH dependence of binding was similar to that reported for the binding of thio-beta-D-digalactoside to the permease. Phosphoenolpyruvate prevented the binding of enzyme IIIglc to the lactose permease in the presence (but not the absence) of the other phosphate transfer components of the phosphotransferase system. These results support the hypothesis that enzyme IIIglc, in its dephosphorylated form, modulates the activity of the lactose permease by a direct protein-protein interaction.